EVALUATION OF FACTORS INFLUENCING LEAKAGE IN PRIMARY INTESTINAL ANASTOMOSIS WITHIN A TERTIARY CARE HOSPITAL: A CROSS-SECTIONAL STUDY. - Utkrisht Kant; Aftab Ahmed (Student’s Journal of Health Research Africa, 2024)
Background Intestinal anastomosis is a procedure carried out widely for various pathological conditions such as benign tumors, malignant tumors, and inflammatory conditions of a certain part of the intestine. The removal of such a part of the intestine requires the joining of the two other parts of the intestine. Postoperatively the occurrence of a leak in this joint can lead to sepsis and increase the occurrence of mortality and morbidity. Method The anastomosis cases of the patients at Sheikh Bhikhari Medical College, Hazaribag are studied retrospectively, and were conducted over two years. 110 cases were reviewed. Clinical and radiological examinations were recorded. The data was statistically analyzed and it was correlated with the occurrence of leakage. Results Among the 110 patients participating in the study it was observed that 10 patients had anastomosis leakage. 50% of the patients with leakage had diabetes. more than 70% of them had undergone either emergency surgery, with a duration of more than 2 hours, and required blood transfusion. 30% of the patients with leakage had colo-colic site surgery. Conclusion In the present study, it was found that patients who had undergone anastomosis with associated comorbidity, of the colo-colic region, with more than 2 hours of surgery, emergency surgeries, and the required blood transfusion during the surgery had higher chances of development of the anastomosis leakage. Recommendation Surgeons should critically analyze the occurrence of anastomosis leakage considering the predisposing risk factors, intraoperative conditions, and site of the surgery.